Certain poor shepherds a Christmas tale - Thomas, Elizabeth Marshall 1931- (Simon & Schuster, 1996)
The story of the Nativity as seen by animals. The protagonists are two sheep dogs and a goat who follow the star to Bethlehem where they are joined by more animals. The novel describes the adventures on the way--they save an angel--and gives their reaction to the birth of Christ.
Keywords: Jesus Christus; Jesus Christ -- Nativity -- Fiction; Animals -- Fiction; Christmas stories; Weihnachten; Fiktionale Darstellung; Christian fiction